Patterns of growth and structural transformation in Africa: Trends and lessons for future development strategies - Timmer, Peter C.; McMillan, Margaret S.; Badiane, Ousmane; Rodrik, Dani; Wouterse, Fleur Stephanie; Binswanger-Mkhize, Hans P. (International Food Policy Research Institute, 2012)
African economies have sustained a solid pace of growth for nearly two decades. This unprecedented performance in the continent’s history is a welcome change from the previous decades of stagnation and decline. So, how can Africa continue to accelerate economic transformation and broaden growth in the decades to come? Solid stewardship of the future development agenda requires a good understanding of the factors shaping the growth process across the continent. More than the average rate of growth, the nature and patterns of structural change or the extent to which individual economies are successfully moving labor and resources into activities with high and increasing levels of productivity, is a much better gauge of future economic performance.